Critical Discourse Analysis of Gender-Based Violence in English Media and Conversations - Rashid, Bushra Ni’ma; Al- Zubaie, Bushra Mahmoud Saleh (Journal of Ecohumanism, 2024)
Globally prominent and inexhaustible, gender and patriarchy have a well-established ambivalent effect on people’s lives as well as the norms of society. Gender-dominated society persists despite efforts to eradicate it, and men are typically the ones who commit it in intimate contexts. This study utilizes the “Socio-Cognitive Approach” and “Critical Discourse Analysis” to look at how gender-based violence is represented in English-language media and discourse. Despite international efforts to eliminate it, gender-based violence goes on to occur, indicating a gap to fill on how it is common and sustained in the media and in everyday discourse.The study is about a great deal of vital social problems, including how gender limitations are introduced and shaped in “discourse and the media”. This researcher poses some questions:What are the different shapes and expressions of it?What social, cultural, and personal elements play a role in it? What are the social, medical, and psychological repercussions? This research hypothesizes the following:Women who confront economic obstacles have poor academic access; Patriarchal power relations can normalize and justify such gender relations; Various elements, encompassing individual and cultural groups contribute to establish male-dominated aspects of gender. Additionally, the influence of these factors can be easily commented upon by effective social practices at distinct stages. The study makes use of Norman Fairclough’s “Critical Discourse Analysis” model and Teun A. van Dijk’s “Socio-Cognitive Approach” to analyze twenty-one spoken texts given by Oprah Winfrey, UN representatives, and “#MeToo activists”. The results support each of the frameworks and show the importance of cultural, systemic, and societal activities by highlighting the role of social cognition and intertextuality as basic discourse items.